Scrutinizing Values-Based Education in Secondary Grade EFL Coursebooks - Ertürk, Gülşah Tikiz (International Dialogues on Education Journal, 2020)
The study aims to expand the understanding of values and values-based teaching in the English language teaching community by scrutinizing English as a foreign language (EFL) coursebooks and the secondary grade curriculum. This is a qualitative study with a document analysis design. The data in the form of EFL coursebooks were examined, interpreted and coded to elicit meaning and gain understanding about the presentation of values residing in four coursebooks. The results of the study indicated that the values presented in secondary level EFL coursebooks do not show an equal distribution and the target values serve the purpose of raising awareness of learners about different values rather than allowing them to understand, internalize and discuss these values at higher levels of learning, which makes the process only superficial. Integrating the teaching of values into the curriculum of language learning classes has been an area of interest in recent years and the Turkish Ministry of Education (MoNE) revised its curriculum in 2018 and textbooks were written in 2019 in accordance with the requirements of the national curricula. Detailed analysis of the teaching of values and their distribution in these coursebooks might help curriculum planners and coursebook writers as well as teachers.